Common Bean Plant Size and Yield in Response to Rates of Foliar-Applied Paclobutrazol, Mepiquat Chloride, and Prohexadione Calcium - de Oliveira, Luan Santos; Soratto, Rogério Peres [UNESP]; Cairo, Paulo Araquém Ramos; da Silva, Leandro Dias; Matsumoto, Sylvana Naomi; Silva, Ricardo de Andrade (Springer Nature, 2023)
Growth retardants have been used as an anti-lodging to reduce shoot growth by blocking the gibberellins biosynthesis without decreasing yield. We hypothesized that the type and dosage of growth retardants vary in effectiveness on reducing vegetative growth and increasing seed yield, as well as that prohexadione calcium (Pro-Ca) may also be an effective growth retardant for common bean (Phaseolus vulgaris L.). The goal of this study was to assess the effects of increasing rates of paclobutrazol (PBZ), mepiquat chloride (MC), and Pro-Ca on common bean morphophysiological and yield traits, based on a field experiment carried out in Vitória da Conquista, northeastern Brazil. Morphophysiological traits were assessed 14 and 38 days after application (DAA) of regulators, and yield traits were assessed at the end of the crop cycle. There was a positive relationship between increasing rates of regulators and decrease in stem length mainly up to 14 DAA, and Pro-Ca was more effective than the other regulators. At 38 DAA, increase in shoot dry mass was recorded when PBZ and MC were sprayed at rates from 100 to 400 g a.i. ha−1. Pro-Ca application increased the height of first pod insertion. Low rates of PBZ (25–50 g a.i. ha−1) increased, whereas high rates of Pro-Ca (200 and 400 g a.i. ha−1) tended to decrease the number of pods per plant. MC reduced the number of empty pods and increased the number of seeds per pod. The 100-seed weight increased up to a peak with an estimated rate of 162.5 g a.i. ha−1 for PBZ, 151.0 g a.i. ha−1 for MC, and 211.8 g a.i. ha−1 for Pro-Ca. PBZ and MC marginally increased seed yield with peaks at the estimated rates of 190.8 and 212.4 g a.i. ha−1, respectively, whereas rates of Pro-Ca greater than 50 g a.i. ha−1 decreased seed yield. The regulators were effective in reducing the plant size, thus mitigating lodging risks in common bean crop with highlight on Pro-Ca, but this regulator at high rates tended to reduce common bean yield.
Keywords: Dry mass partitioning; Lodging; Phaseolus vulgaris; Plant growth retardant